Afaltoxin M1 Contamination in Some Mothers Breast Milk in the City of Erbil - Qadir, Avan Farouq; Ali, Mouafaq Mohamad (Sulaimani Journal for Pure and Applied Sciences, 2014)
Aflatoxin is a carcinogenic compound with high toxicity levels and is one of mutagens factors that have adverse effects on many vital body events, in addition to its effect on the body immune system. To study the occurrence of aflatoxin M1 (AFM1) in the mother’s milk that depend on breast and mixed lactation, in the governorate of Erbil, 20 milk samples were collected from Rezgari hospital of Erbil city. The aflatoxins estimation has been done using the TLC method. The results showed the presence of AFM1 in 16 samples (80% of total samples) with the range of 0.1-3.01 μg/l. When comparing the results with the internationally acceptable values, it shows that most of the obtained results were much higher than the value limits depending on the U.S. FDA and European Union regulations as well.
Keywords: aflatoxin M1 breast milk TLC method